Determining neutrino oscillation parameters from atmospheric muon neutrino disappearance with three years of IceCube DeepCore data - Sarkar, S; Aartsen, MG (American Physical Society, 2015)
We present a measurement of neutrino oscillations via atmospheric muon neutrino disappearance with three years of data of the completed IceCube neutrino detector. DeepCore, a region of denser instrumentation, enables the detection and reconstruction of atmospheric muon neutrinos between 10 GeV and 100 GeV, where a strong disappearance signal is expected. The detector volume surrounding DeepCore is used as a veto region to suppress the atmospheric muon background. Neutrino events are selected where the detected Cherenkov photons of the secondary particles minimally scatter, and the neutrino energy and arrival direction are reconstructed. Both variables are used to obtain the neutrino oscillation parameters from the data, with the best fit given by $Δ m^2_{32}=2.72^{+0.19}_{-0.20}× 10^{-3}\,eV^2$ and $\sin^2θ_{23} = 0.53^{+0.09}_{-0.12}$ (normal mass hierarchy assumed). The results are compatible and comparable in precision to those of dedicated oscillation experiments.